Effect of different feed ingredients on digestive enzymes activity and on the histology of liver and intestine in Labeo rohita Hamilton, 1822 - Iqbal, K. Javed; Ashraf, Muhammad; Javid, Arshad; Chaudhry, M. S.; Khan, Noor; Majeed, Hamid; Abbas, Farzana; Hafeez-Ur-Rehman, M.; Rasool, Fayyaz; Altaf, Muhammad; Baboo, Irfan (Indian Journal of Fisheries, 2018)
Present study compared the effect of fishmeal and selected plant-origin feed ingredients on digestive enzymes activity as well as on the histology of liver and intestine in Labeo rohita. Guar meal (GM), soybean meal (SBM), cotton seed meal (CSM) and canola meal (CM) were used as experimental feed ingredients in the four treatment diets, while fishmeal (FM) incorporated diet served as control. There were three replicates for each of the treatment and control diets. The experiment was conducted in 15 fiber glass tanks, each having 10 fish. Fish in each tank was fed @ 4% of body weight. Protease activity varied significantly (p<0.05) between anterior and posterior part of the intestine while amylase and lipase activities of whole intestine differed significantly (p<0.05) between the treatments. Maximum lipase activity was observed in fish fed with GM while minimum with CM ingredients. Vacuolation of hepatocytes and some variations in the mid intestine were also observed in response to different feed ingredients. Protease activity was greater throughout the intestinal tract when fish were fed with CSM and FM diets. Results of the present study indicated that CSM and FM are better ingredients for feed formulation for L. rohita.